Multidisciplinary Treatment Strategies for Wilms Tumor: Recent Advances, Technical Innovations and Future Directions - Theilen, Till-Martin; Braun, Yannick; Bochennek, Konrad; Rolle, Udo; Fiegel, Henning C.; Friedmacher, Florian (Frontiers in Pediatrics, 2022)
Significant progress has been made in the management of Wilms tumor (WT) in recent years, mostly as a result of collaborative efforts and the implementation of protocol-driven, multimodal therapy. This article offers a comprehensive overview of current multidisciplinary treatment strategies for WT, whilst also addressing recent technical innovations including nephron-sparing surgery (NSS) and minimally invasive approaches. In addition, surgical concepts for the treatment of metastatic disease, advances in tumor imaging technology and potentially prognostic biomarkers will be discussed. Current evidence suggests that, in experienced hands and selected cases, laparoscopic radical nephrectomy and laparoscopic-assisted partial nephrectomy for WT may offer the same outcome as the traditional open approach. While NSS is the standard procedure for bilateral WT, NSS has evolved as an alternative technique in patients with smaller unilateral WT and in cases with imminent renal failure. Metastatic disease of the lung or liver that is associated with WT is preferably treated with a three-drug chemotherapy and local radiation therapy. However, surgical sampling of lung nodules may be advisable in persistent nodules before whole lung irradiation is commenced. Several tumor markers such as loss of heterozygosity of chromosomes 1p/16q, 11p15 and gain of function at 1q are associated with an increased risk of recurrence or a decreased risk of overall survival in patients with WT. In summary, complete resection with tumor-free margins remains the primary surgical aim in WT, while NSS and minimally invasive approaches are only suitable in a subset of patients with smaller WT and low-risk disease. In the future, advances in tumor imaging technology may assist the surgeon in defining surgical resection margins and additional biomarkers may emerge as targets for development of new diagnostic tests and potential therapies.